Energy Efficient Speed and Position Control of Electric Drives with Pmsm - Vittek, Jan; Ftorek, Branislav (Communications - Scientific letters of the University of Zilina, 2014)
A new speed and position controller respecting principles of near-energy optimal control for the drives with permanent magnet synchronous motor are developed as a contribution to the energy saving and environmental protection. Two various approaches to the energy saving controller design are analysed. The first approach is strictly based on energy optimal control theory and derives analytical solutions of the control problem. The second approach develops approximated solution for the drive position controller when the optimal speed trajectory is modified to correspond to the triangular and trapezoidal profile. This approach enables not only to compare energy demands of the individual control system design but also to exploit near-energy optimal controller for any controlled industrial drive